Description of a Simple Model for the Study of Bone Calcium Metabolism - Pedroli, G.; Roncari, G.; Rapisardi, L.; Conte, L. (Nuklearmedizin - NuclearMedicine, 1980)
A simple model for the study of bone calcium metabolism is proposed. It describes the kinetics of a radioactive tracer in terms of an open single compartment system with an expanding volume for a finite period of time. In addition to the simplicity of the hypotheses introduced, the model is able to give a good description of the biological processes which regulate calcium kinetics. Moreover the functional parameters can be easily calculated, even just graphically. 15 normal subjects and 22 patients affected by various bone diseases were studied. The results were compared with those obtained by using the model proposed by Burkinshaw et al. and the method described by Reeve et al.